Fuel consumption and emission analysis of harbour vessels - Chen, Zhongshuo (Nanyang Technological University, 2023)
To mitigate global warming and pollution issues, the maritime industry is endeavouring to reduce ship fuel consumption and emissions, as well as explore alternative marine fuels such as a promising alternative fuel, hydrogen. Among various measures, two of the ways of reducing emissions from ships are: reducing fuel consumption and adopting cleaner marine fuels. Hence, accurately predicting fuel consumption and emissions can reveal the truth of the current situation and provide suggestions for daily operations. Furthermore, the adoption of alternative marine fuels should be considered and investigated regarding the energy consumption, potential costs, and environmental impact. This thesis aims to study fuel consumption and emissions based on the current diesel-powered and potential hydrogen-powered scenarios for harbour vessels, which are largely neglected in literature but play essential roles in the maritime industry. First, machine learning models were proposed for predicting harbour vessel fuel consumption and emissions. A statistical regression method for prediction of the fuel consumption and a bottom-up method for estimation of the emissions were considered as the baseline methods. The superiorities of the proposed models were illustrated using two cases of harbour vessels operating within the Singapore port. Among the four models for predicting fuel consumption, the Random Forest model outperformed the other three models. It also found that collectively adding meteorological factors as input variables enhanced the prediction accuracy. Compared to the baseline method, the proposed model for predicting the emissions obtained up to 48% and 62% improvements in prediction accuracy for nitrogen oxides and carbon monoxide emissions, respectively. The proposed models can provide good prediction accuracy and assist stakeholders in better understanding and managing the current situation, which principally utilises diesel fuel on harbour vessels. Second, the energy consumption, potential costs, and environmental impact of harbour vessels were investigated when adopting hydrogen as a fuel. The analyses were conducted with a case study of a tugboat. A discrete event simulation model was built based on an operational profile of the tugboat, and comparative cost analyses of diesel-powered tugboats and hydrogen-powered tugboats were conducted for current and future scenarios. As the results showed, hydrogen-powered tugboats can save about 76% of fuels in terms of quantity than diesel-powered tugboats. The cost break-even point of hydrogen fuel cell systems and diesel engines would occur in 2037. Moreover, a comparative life cycle assessment study was conducted to evaluate the environmental impact of two power systems (hydrogen fuel cells and diesel engines) in tugboats. Around 83.9% (GWP20a) to 85% (GWP100a) of global warming impact can be reduced when adopting hydrogen-powered tugboats compared with a diesel tugboat. Furthermore, recycling materials in the decommissioning stage will reduce the overall environmental burden for both power systems, varying from 8.5% to 44%. Nevertheless, exposure to toxic substances of processes in the hydrogen fuel cell manufacturing and hydrogen fuel supply stages, especially in marine aquatic, will increase compared with diesel tugboats. The results can serve as references for the maritime industry when considering the adoption of hydrogen.